16.5k views
2 votes
Let f(x) = e ^ (6x) and g(x) = 8in(x) Find and simplify g(f(- 2)) -96 -48 48 C B A

User Jon Rimmer
by
5.4k points

2 Answers

5 votes

Answer: g(f(-2))=-96

Explanation:


Given: \ f(x)=e^(6x)\ \ \ \ g(x)=8ln(x)\ \ \ \ g(f(-2))=?\\\\f(-2)=e^(6*(-2))\\\\f(-2)=e^(-12)\\\\Hence,\\\\g(f(-2))=8ln(e^(-12))\\\\g(f(-2))=8*(-12)\\\\g(f(-2))=-96

User Adad Dayos
by
5.8k points
3 votes

Answer:

-96

Explanation:

Given:


\begin{cases}f(x)=e^(6x)\\ g(x)=8 \ln (x) \end{cases}

To find g[f(-2)], substitute x = -2 into the function f(x):


\implies f(-2)=e^(6 * -2)=e^(-12)

Then substitute the function f(-2) in place of the x in function g(x):


\implies g[f(-2)]=8 \ln \left(e^(-12)\right)


\textsf{Apply the power law}: \quad \ln x^n=n \ln x


\begin{aligned}\implies g[f(-2)]&=-12\cdot 8 \ln \left(e\right)\\&=-96 \ln \left(e\right)\end{aligned}

Apply the log law: ln(e) = 1


\begin{aligned}\implies g[f(-2)]&=-96 \ln \left(e\right)\\&=-96(1)\\&=-96\end{aligned}

---------------------------------------------------------------------

As one calculation:


\begin{aligned}g[f(-2)]&=8 \ln \left(e^(6 * -2)\right)\\& = 8 \ln \left(e^(-12)\right)\\& = -12 \cdot 8 \ln \left(e\right)\\& = -96(1)\\& = -96\end{aligned}

User VivekRajendran
by
6.0k points